The 50 Greatest Books of All Time - Reaction - Benjamin McEvoy (2022)
📚 Read the Great Books with Hardcore Literature: https://www.patreon.com/hardcoreliter... ———————————— 🎙️ https://open.spotify.com/show/70IZA24... (Subscribe to the Hardcore Literature Podcast on iTunes & Spotify) 🏫 https://hardcore-university.teachable... (Hardcore University, Exam Preparation Courses) ✍🏼 https://benjaminmcevoy.com My Personal Website ———————————— Hardcore Literature Lecture Series ———————————— 📔Contents Page: https://cutt.ly/CmNhRY3 🎖️ War and Peace: https://cutt.ly/U3nzGma 🎭 Shakespeare Project: https://cutt.ly/B3nxHH7 🐳 Moby Dick: https://cutt.ly/K3nzVKf ☄️ Blood Meridian: https://cutt.ly/P3nz6Qp 🍂 Wuthering Heights: https://cutt.ly/N3nxxYt 🇮🇪 Ulysses: https://cutt.ly/x3nxQmN 🚂 Anna Karenina: https://cutt.ly/vmNhAWv 💀 Crime and Punishment: https://cutt.ly/rmNhFt5 ⚓ Persuasion: https://cutt.ly/amNhX7b ☕ In Search of Lost Time: https://cutt.ly/5mNh8oD ⚔️ The Hero’s Journey: https://cutt.ly/UmNjrE3 🌸 Siddharta: https://cutt.ly/YmNjuzi 🎠 Don Quixote: https://cutt.ly/cmNjoK4 ❤️Shakespeare’s Sonnets: https://cutt.ly/nmNlW7V 🇫🇷 Les Misérables: https://cutt.ly/J3YixoA 🕯️ The Turn of the Screw: https://cutt.ly/nToAQQ3 🖋️ Dickens Seasonal Read: https://cutt.ly/9ToAybt 📖 Middlemarch Serial Reading: https://tinyurl.com/45rv965c ———————————— 0:00 the 50 greatest books list 1:22 books 50-45 8:58 books 44-40 16:13 books 40-35 22:24 books 34-30 25:56 books 29-25 30:56 books 24-20 35:18 books 19-15 39:37 books 14-10 43:37 books 9-5 48:50 books 4-3 51:06 books 2-1 55:52 my thoughts on this list
Keywords: literature